A novel screening method for rice allelopathic potential: the inhibitory‐circle method. (7th June 2015) - Li, J Y; Guo, X K; Zhang, Q; Liu, C H; Lin, Z H; Yu, Z M; Wu, H; He, H B; Hatcher, Paul
Summary Screening crop accessions for allelopathic activity is of paramount importance for crop allelopathy research. Previous bioassays often did not use a mixed culture of donor and target plants, did not use soil and were not conducted under natural conditions. In this study, we designed an inhibitory‐circle method in which a rice accession (donor plant) and Echinochloa crus‐galli (target plant) were cultured together in paddy soil under natural conditions. First, we determined that the highest allelopathic activity of allelopathic rice accession PI312777 was at the 5‐leaf stage, and the suitable distance of rice seedlings and E. crus‐galli was 12 cm apart. This method was then validated by a field test. A further 40 rice accessions were evaluated for allelopathic activity to E. crus‐galli using this method. Two rice accessions, PI312777 and Taichung Native 1, had highly allelopathic activity to E. crus‐galli (inhibitory rate > 50%), while another accession, Lemont, had non‐allelopathic activity. These experimental results were in accordance with previous studies using direct field experiments. The inhibitory‐circle method integrated three necessary conditions, that is donor and target plants grown together, with soil as the medium and under natural conditions for reliable results. The 'inhibitory‐circle method', which combined donor and target plants, soil medium and field conditions, can give reliable results in one step, compared with laboratory screening methods. Also, the 'inhibitory‐circle method' gave results in 30‐35 days, thereby substantially reducing the requirements for time, labour and cost.